Growth curves for ostriches (Struthio camelus) in a Brazilian population - Ramos, S. B. [UNESP]; Caetano, S. L. [UNESP]; Savegnago, R. P. [UNESP]; Nunes, B. N. [UNESP]; Ramos, Alcides Amorim [UNESP]; Munari, D. P. [UNESP] (My University, 2013)
The objective of this study was to fit growth curves using nonlinear and linear functions to describe the growth of ostriches in a Brazilian population. The data set consisted of 112 animals with BW measurements from hatching to 383 d of age. Two nonlinear growth functions (Gompertz and logistic) and a third-order polynomial function were applied. The parameters for the models were estimated using the least-squares method and Gauss-Newton algorithm. The goodness-of-fit of the models was assessed using R2 and the Akaike information criterion. The R2 calculated for the logistic growth model was 0. 945 for hens and 0. 928 for cockerels and for the Gompertz growth model, 0. 938 for hens and 0. 924 for cockerels. The third-order polynomial fit gave R2 of 0. 938 for hens and 0. 924 for cockerels. Among the Akaike information criterion calculations, the logistic growth model presented the lowest values in this study, both for hens and for cockerels. Nonlinear models are more appropriate for describing the sigmoid nature of ostrich growth. © 2013 Poultry Science Association Inc.
Keywords: Growth; Nonlinear models; Ostrich; Struthio camelus; aging; agriculture; animal; biological model; Brazil; growth, development and aging; ostrich; physiology; Aging; Agriculture; Animals; Models, Biological; Struthioniformes; Animalia